Desperate measures [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2018)
Stone Barrington is ready for anything, and up against a problem that could cost him everything, in the newest thriller from perennial fan favorite and number one New York Times best selling author Stuart Woods.